Effect of Human Serum Albumin on the Kinetics of N-Glutaryl-L-Phenylalanine P-Nitroanilide Hydrolysis Catalyzed by ?-Chymotrypsin - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Ahumada-Escandon, M; Ahumada-Escandon, M; Abuin-Saccomano, E (2011)
The effect of human serum albumin (HSA) addition on the rate of hydrolysis of N-glutaryl-L-phenylalanine p-nitroanilide (GPNA) catalyzed by ?-chymotrypsin has been measured in phosphate buffer saline at pH = 7.4. The presence of HSA (up to 200 ?M) leads to a decrease in the rate of the process. The reaction follows a Michaelis-Menten mechanism under all the conditions employed. To take into account the effect of substrate depletion due to its binding to albumin ultrafiltration experiments were carried out from which the binding of GPNA to HSA was derived. After correction of the kinetic data taking into account the binding of GPNA to HSA, the activity of the enzyme, and the derived Michaelis constant and catalytic rate constant tends to remain almost independent of the presence of albumin, indicating that the depletion of the substrate due to its binding to HSA is the main factor affecting the enzyme activity. © Springer Science+Business Media, LLC 2011.